Numerical Simulation of the Effect of Blade Shape on Vertical Axis Wind Turbine Using NACA 0015, NACA 4415, and NACA 7510 - Rezki Alhakim; Randi Purnama Putra; Yolli Fernanda; Fitrah Qalbina (Jurnal Vokasi Mekanika (VoMek), 2026)
Energy is a resource that can be used to perform various tasks, including fuel, electricity, mechanical energy, and heat. With technological advances and global economic development, the demand for electricity will continue to increase. This drives various research efforts towards alternative energy sources, ranging from the development of existing tools to the creation of new innovations. Wind turbines work by utilizing the kinetic energy of the wind flow to rotate the blades, which are then converted into electrical energy through a generator system. The purpose of this study is to analyze the effect of curvature shape on the Lift Coefficient (Cl), Drag Coefficient (Cd), and Power Coefficient (Cp) of vertical axis wind turbine blades. Simulations were carried out in 3D using ANSYS Fluent software and the SST turbulence model, with wind speeds ranging from 4 to 7 m/s. The aerodynamic profiles analyzed were NACA 0015, NACA 4415, and NACA 7510. Aerodynamic simulations of vertical axis wind turbines were carried out using a steady-state approach with a multi-reference frame (MRF) rotation model to obtain the average aerodynamic characteristics of the rotor. The simulation results show that NACA 4415 produces the best Cl value with relatively controlled Cd, while NACA 0015 shows the worst aerodynamic performance. NACA 7510 produces the highest Cp value at all wind speed variations, despite low Cl and high Cd values, indicating that the drag mechanism dominates torque generation at low speeds.